Dietary glycemic index and glycemic load during pregnancy and offspring risk of congenital heart defects: a prospective cohort study. Issue 3 (14th January 2020) - Schmidt, Amalie Bøggild; Lund, Marie; Corn, Giulia; Halldorsson, Thorhallur I; Øyen, Nina; Wohlfahrt, Jan; Olsen, Sjurdur F; Melbye, Mads
ABSTRACT: Background: Prepregnancy diabetes, especially when severely dysregulated, is associated with an increased risk of congenital heart defects in offspring. This suggests that glucose plays a role in embryonic heart development. Objective: The aim was to investigate the association between midpregnancy dietary glycemic index (GI), glycemic load (GL), and sugar-sweetened beverages and the risk of congenital heart defects in the offspring. Methods: Offspring of mothers from the Danish National Birth Cohort who filled out a food-frequency questionnaire (FFQ) covering midpregnancy dietary intake were included. Individual-level information on GI and GL, offspring congenital heart defects, and health and lifestyle covariates was linked. The association between GI and GL and offspring congenital heart defects was estimated by logistic regression. Further, we evaluated whether maternal intake of sugar-sweetened drinks increased the risk of offspring congenital heart defects. Results: In total, 66, 387 offspring of women who responded to the FFQ were included; among offspring, 543 had a congenital heart defect. The adjusted OR (aOR) of congenital heart defects among offspring of mothers belonging to the highest versus the lowest GI quintile was 1.02 (95% CI: 0.78, 1.34; P -trend = 0.86). Results were similar for GL (aOR: 0.95; 95% CI: 0.72, 1.24). A high intake of sugar-sweetened carbonated beverages was associated with a statistically significant increased risk of offspring congenital heart defects (highest vs lowest intake—aOR: 2.41; 95% CI: 1.26, 4.64; P -trend = 0.03). No association was found with other types of beverages. Conclusions: The study does not support an association between a high GI and GL in midpregnancy and increased offspring risk of congenital heart defects. Nevertheless, a statistically significant association between sugar-sweetened carbonated beverages and a moderately increased risk of offspring congenital heart defects was observed.